Humble Leadership and Employee Resilience: Exploring the Mediating Mechanism of Work-Related Promotion Focus and Perceived Insider Identity - Zhu, Yanhan; Zhang, Shuwei; Shen, Yimo (Frontiers in Psychology, 2019)
Although the topic of employee resilience has received increasing attention recently, extant research has largely failed to explore its situational triggers. Drawing on social information processing theory, this research integrates the literature of humility and resilience to theorize the underlying mechanism through which humble leadership facilitates employee resilience. This research proposes a potential heterogeneous effect that humble leadership catalyzes employee resilience through multiple pathway. A field study (N = 434) and an experimental study (N = 104) conducted in China Mainland, support hypotheses that humble leadership enhances employee resilience through increased work-related promotion focus and perceived insider identity simultaneously. Research implications are discussed and directions for future research are offered.